Anemia in early congenital syphilis - А. V. Vislobokov; R. A. Khmel'nitskij (Vestnik Dermatologii i Venerologii, 2021)
The determination of blood parameters allowed us to establish that anemia develops in a number of infectious diseases, which is called "anemia of inflammation" or anemia of chronic diseases. The article presents a rare clinical case of the development of anemia of the inflammatory response, accompanied by a marked decrease in the content of hemoglobin (less than 110 g/l), hematocrit (less than 30%) and red blood cells (less than 3,0 х 1012/l), in a child with early congenital syphilis with symptoms of: specific rhinitis, papular infiltration, pemphigus, hepatosplenomegaly and damage to the nervous system. As a result of specific treatment with water-soluble benzylpenicillin salt at the rate of 100 U/kg of body weight for 28 days, and transfusion of erythrocyte mass of 15 ml/kg of child weight, there was a parallel regression of clinical manifestations of syphilis with positive dynamics of serological reactions and restoration of the number of red blood cells and the concentration of hemoglobin in the blood.